Arterite temporal com comprometimento das glândulas salivares Temporal arteritis associated with salivary glands enlargement and depressive syndrome: a case report - Lineu C. Werneck; Affonso Coelho (Arquivos de Neuro-Psiquiatria)
E relatado um caso de arterite temporal em paciente com crises de cefaléia paroxística associadas a síndrome depressiva e, na última crise, a aumento de volume das glândulas salivares. Biopsia de artéria temporal superficial mostrou aspecto típico de arterite, com células gigantes mononucleadas. A cefalalgia e o aumento de volume das glândulas salivares regrediram mediante a administração de corticoesteróides. A case of temporal arteritis associated with depressive syndrome and enlargement of salivary glands is reported. Biopsy of the superficial temporal artery showed arteritis with multinucleated giant cells. After corticosteroid therapy the headache and the enlargement of the salivary gland improved rapidly.